Bmp signaling in colonic mesenchyme regulates stromal microenvironment and protects from polyposis initiation. Issue 11 (10th February 2016) - Allaire, Joannie M.; Roy, Sébastien A.B.; Ouellet, Camille; Lemieux, Étienne; Jones, Christine; Paquet, Marilène; Boudreau, Francois; Perreault, Nathalie
Abstract : In the colon, myofibroblasts are primary contributors in the establishment of the microenvironment involved in tissue homeostasis. Alterations in myofibroblast functions lead to changes resulting in a toxic microenvironment nurturing tumorigenesis. Bone morphogenetic proteins (Bmps) are morphogens known to play key roles in adult gut homeostasis. Studies in genetically‐modified mice have shown that Bmp disruption in all cell layers leads to the development of gut polyposis. In contrast, our studies showed that loss of Bmp exclusively in the gastrointestinal epithelium resulted in increased epithelial proliferation without polyposis initiation, thus suggesting a key role for mesenchymal Bmp signaling in polyposis initiation. In order to identify the role of mesenchymal Bmp signaling on the microenvironment and its impact on colonic mucosa, a mouse model was generated with suppression of Bmp signaling exclusively in myofibroblasts ( Bmpr1a ΔMES). Bmpr1a ΔMES mice exhibited increased subepithelial proliferation with changes in cellular composition leading to the development of a primed stroma with modulation of extracellular matrix proteins, immune cells and cytokines as early as 90 days of age. This microenvironmental deregulation was associated with increased polyposis initiation at one year of age. These results are the first to demonstrate that mesenchymal Bmpr1a inactivation alone is sufficient to prompt an expansion of myofibroblasts leading to the development of a reactive mesenchyme that contributes to polyposis initiation in the colon. These findings support the novel concept that inhibition of Bmp signaling in mesenchymal cells surrounding the normal epithelium leads to important changes instructing a toxic microenvironment sufficient to induce colonic polyposis. Abstract : What's new? Colorectal cancer develops from polyps in the intestinal epithelium. Bmps are growth factors that are known to protect against colorectal tumorigenesis, presumably by interacting with cells in this epithelial layer. In this study, however, the authors found that Bmp signaling in mesenchymal cells is crucial for maintaining a normal microenvironment surounding the epithelium. Loss of Bmp signaling in these mesenchymal cells creates a toxic microenvironment which can, in turn, lead to the formation of colorectal polyps with the potential to become malignant.